ROLE OF BANKS AS FINANCIAL SUCCOR AMID COVID FIGHT: AN INDIAN PERSPECTIVE - Chatterjee, Deboshree; Sekhar, Savanam Chandra; Babu, M. Kishore (Indian Journal of Finance and Banking, 2022)
At present time, the existence of Coronavirus in the environment continues to bother the globe. As an aftermath effect, the entire economies are at a standstill. Reduced economic activities, mass unemployment, and financial crunch have emerged as the most realistic prospects and so, people are struggling for their livelihoods. Whether it’s developed, developing, or underdeveloped economies, no country could save them from its tragic consequences. The economy of India has also been severely affected due to this pandemic. Amid this situation, the role of banks has become more evident in the public eyes in recent times. The banking sector is the spine of the country’s economy. As a result, common people started expecting banks to step forward as financial succor for them in these difficult times. The current paper tries to put the spotlight on the significant roles of the banks in supporting the people, the lives, and the economies in this unpredicted state of affairs. The study offers an analysis of secondary data which is gathered from different research articles published on the Covid-19 outbreak. Further, this paper offers suggestions to Indian banks on the adoption of innovative strategies for the improvisation of financial lives and the economy.JEL Classification Codes: E50, G20, G21, I10, P36.